2016
DOI: 10.1177/1538574416682159
|View full text |Cite
|
Sign up to set email alerts
|

Below-Knee Amputation Failure and Poor Functional Outcomes Are Higher Than Predicted in Contemporary Practice

Abstract: Despite a perceived functional bias toward knee salvage at the time of major amputation, most patients failed to postoperatively ambulate. Those with decreased TcPO2 levels (<40 mm Hg) have a 2-fold higher risk of AKA conversion or death, while nearly one-fourth of all BKA patients will succumb to the same fate irrespective of TcPO2. This suggests that many BKA patients in the endovascular era fail to derive the perceived benefit of knee salvage at the time of their index amputation. These findings highlight t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 25 publications
2
19
0
Order By: Relevance
“…Amputation‐level decision‐making in the context of diabetes and peripheral artery disease (PAD) is extremely challenging. The preservation of mobility and its impact on quality of life are key considerations. The goal of preserving mobility has led to a focus on attempting the most distal amputation procedure possible: preserving the knee joint by performing a transtibial (TT) rather than a transfemoral (TF) amputation, or by attempting a limb salvage transmetatarsal (TM) amputation rather than a major amputation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Amputation‐level decision‐making in the context of diabetes and peripheral artery disease (PAD) is extremely challenging. The preservation of mobility and its impact on quality of life are key considerations. The goal of preserving mobility has led to a focus on attempting the most distal amputation procedure possible: preserving the knee joint by performing a transtibial (TT) rather than a transfemoral (TF) amputation, or by attempting a limb salvage transmetatarsal (TM) amputation rather than a major amputation.…”
Section: Introductionmentioning
confidence: 99%
“…The preservation of mobility and its impact on quality of life are key considerations. The goal of preserving mobility has led to a focus on attempting the most distal amputation procedure possible: preserving the knee joint by performing a transtibial (TT) rather than a transfemoral (TF) amputation, or by attempting a limb salvage transmetatarsal (TM) amputation rather than a major amputation. The importance of preserving extremity length by performing more distal amputations, especially at the TM level, has been questioned because of the associated risk of healing failure and the uncertainty about potential mobility advantages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…70 A separate study found that 25% of BKAs ultimately required conversion to an AKA. 71 Functional outcomes following major amputation are largely dependent on preoperative comorbidities and functional status. Younger, ambulatory patients with fewer comorbidities can generally be expected to have functional outcomes similar to those with successful revascularization.…”
Section: The Impact and Outcomes Of Major Amputationmentioning
confidence: 99%
“…This permits noninvasive evaluation of microcirculation in a local region through analysis of TcPO2 [14][15][16]. TcPO2 is commonly used as a predictor for wound healing potential in ulcer cases or for the determination of adequate amputation levels [17][18][19][20][21][22][23][24][25]. For example, a TcPO2 value of <40 mmHg has been associated with poor healing outcomes in persons with a transtibial amputation and a two-fold higher risk in requiring conversion to a transfemoral amputation [20].…”
Section: Introductionmentioning
confidence: 99%